A Description of a Noninvasive Surgical Training Pathway Using Translational Tools to Teach Intracoelomic Implantation of Acoustic Transmitters in Fish. Issue 3 (19th July 2018) - Brosnan, Ian G.; Williams, Wendy O.; Sanders, George E.; McGarry, Louise P.; Greene, Charles H.
Abstract: Researchers engaged in surgical implantation of acoustic transmitters into fish must receive adequate and appropriate training to ensure the welfare of their subjects and the quality of the data collected. Increasingly, researchers are being encouraged to partner with veterinarians to improve training and to consider the principles of animal welfare in training. Here, we describe a five‐stage training pathway, including implementation of new training tools (the Translational Training Tools and field certification), that was developed collaboratively by researchers and veterinarians and addresses the "three Rs" of animal welfare in the context of surgical training. The three Rs include animal replacement, reduction of the number of animals used, and refinement of techniques to decrease or eliminate pain or distress. The Translational Training Tools, described in the context of the training pathway, use tools as replacement models during training to reduce the number of animals used and allow for refinement of surgical skills prior to working on live animals. The purpose of this paper is to document the Translational Training Tools and the training pathway, which will be useful in developing de novo protocols for review by Institutional Animal Care and Use Committees and similar bodies.